The Testing of Diana Mallory - Ward, Humphry, Mrs., 1851-1920; Hatherell, William, 1855-1928 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Testing of Diana Mallory" by Mrs. Humphry Ward is a novel written during the early 20th century. The story introduces Diana Mallory, a young woman who has recently returned to England after living abroad with her father. As she begins to settle into a charming old house called Beechcote Manor, the narrative explores her yearning for connection to her homeland and the complex emotions that accompany her status as an orphan and a newcomer in both society and her own life. The opening of the novel captures Diana's emotional state through descriptive prose, showcasing her impressions of the English countryside as she revels in the nostalgic beauty of her surroundings. As she gazes at the morning landscape, she reflects on her past experiences abroad, and her feelings of both joy and melancholy intertwine. The narrative also highlights her first interactions with her new companion, Mrs. Colwood, and the warmth of village life, hinting at Diana's desire to form relationships within this new social setting. As she navigates her place in a world filled with both hope and challenges, Diana is portrayed as a spirited and introspective character, who is aware of her longing for acceptance, connection, and identity against the backdrop of her English heritage. (This is an automatically generated summary.)
Release date is 2004-09-14
E-text prepared by Juliet Sutherland, Charlie Kirschner, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Young women -- Fiction; Love stories